How to choose a non-manipulable delegation? - Burak Can; Péter Csóka; Emre Ergin (Hungarian Academy of Sciences, Institute of Economics, 2017)
This paper analyzes how to choose a delegation, a committee to represent a society such as in a peace conference. We propose normative conditions and seek optimal, consistent, neutral, and non-manipulable ways to choose a delegation. We show that a class of threshold rules are characterized by these criteria. The rules do not choose a fixed number of delegates, but instead require different sizes of delegations, depending on the heterogeneity in society. Therefore the resulting delegations are very inclusive, and with t delegates the ratio of individuals whose opinions are not included is always below (0:5)t, following the well-known Zeno's dichotomy. For instance a delegation of size 2 should have at least 75% support from the society and therefore only less than 25% of the opinion pool can be neglected.
Keywords: C70; D71; 330; Aggregation Rules; Committee Selection; Conflict Management; Kemeny Distance; Strategy-proofness